Implementasi Sistem Rekomendasi Tipe Rumah Menggunakan Metode Naïve Bayes - Iqbal, Mohammad; AjiAji, Bernadus Anggo Seno; Rahmanti, Farah Zakiyah (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
This research aims to overcome the challenges faced in the marketing sector, where data recording is still done manually, which can lead to data loss and time inefficiencies in the department. Finance department organizes data. Data used in this study were collected through stakeholder interviews and direct field observations. The data used for Naïve Bayes classification were obtained from the results of questionnaires completed by buyers, with a total of 62 data collected. The information system proposed in this study is built on a web platform using MySQL database and PHP programming language, using Laravel Framework. To understand the system flow in a structured way, architectural diagrams are used, while functional workflows are explained using diagrams. The result of this research is to design a system that can help housing development companies manage management and make house type recommendations to potential buyers.